Effects of erythropoietin administration in training athletes and possible indirect detection in doping control - Audran, M.; Gareau, R.; Matecki, S.; Durand, F.; Chenard, C.; Sicart, M. T.; Marion, B.; Bressolle, F. (Medicine & Science in Sports & Exercise, 1999)
This study investigated the effects of repeated subcutaneous injection of rHuEpo (50 IU·kg-1) in athletes and proposes a method based on the measurement in blood samples of the sTfR/serum protein ratio to determine if the observed values of this marker are related to rHuEpo abuse. Result: When oxygen uptake measured at the VT was expressed as a percentage of VO2 max, the values obtained were also significantly higher. The increased values of Tfr and sTfr/serum proteins, respectively, above 10 µg·mL-1 and 153, indicated the probable intake of rHuEpo.